2019
DOI: 10.1111/jch.13704
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of miRNA 145 and up‐regulation of miRNA 4516 may be associated with primary hypertension

Abstract: Complex mechanisms including genetic factors have been proposed in the pathogenesis of primary hypertension (HT). Micro RNAs (miRNAs) are single‐stranded RNA molecules that are not converted into protein products. However, it has been established that genes regulate conversion into protein products. The primary aim of this study was to investigate the roles of miRNA 4516, miRNA 145, miRNA 24, and miRNA 181a in the pathogenesis of HT. The secondary aim was to investigate the relation between these miRNAs and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…Furthermore, the significant relationship between miR-30a-5p expression and screen-detected and known HPT was demonstrated. Several studies have reported on a number of dysregulated miRNAs in HPT using different tissues, but results remain inconsistent (21)(22)(23)(24)(25). A study similar to ours reported 27 dysregulated miRNAs in a sample of 13 individuals with HPT (21), although the miRNAs were not similar to ours.…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, the significant relationship between miR-30a-5p expression and screen-detected and known HPT was demonstrated. Several studies have reported on a number of dysregulated miRNAs in HPT using different tissues, but results remain inconsistent (21)(22)(23)(24)(25). A study similar to ours reported 27 dysregulated miRNAs in a sample of 13 individuals with HPT (21), although the miRNAs were not similar to ours.…”
Section: Discussioncontrasting
confidence: 60%
“…Thousands of miRNAs have been identified in humans, animals, and plants. Given their ubiquity, miRNAs have been extensively studied and proven to contribute to pathological conditions, such as hypertension (Biancardi & Sharma, 2020; Li et al, 2018; Ozkan et al, 2019). However, research on the relationship between miRNAs and the neurogenic pathogenesis of hypertension is limited.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of reports have shown that miRNA contributes to many pathological and physiological processes (Ali Syeda et al, 2020; Cakmak & Demir, 2020; Juźwik et al, 2019; Bhaskaran & Mohan, 2014). Several miRNAs, such as miRNA‐21, miRNA‐145, miRNA‐4516, and miRNA‐181a, have been proven to be associated with hypertension (Biancardi & Sharma, 2020; Li et al, 2018; Ozkan et al, 2019). However, few researchers have looked into the miRNA profiles of the RVLM and their effects on sympathetic activation and blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…RUNX1 [449], CAV1 [472], STAT6 [468], CDKN2A [226], HSPA2 [485], hsa-mir-10b-5p [617] and HOXA5 [618] were related to the obesity. RUNX1 [511], CAV1 [534], CACNA1A [543], STAT6 [528], CDKN2A [105], hsa-mir-4516 [619], SRY (sex determining region Y) [620], FOXC1 [621] and PRDM1 [622] might offer useful information for treating hypertension. CAV1 [303], CACNA1A [307], IRS4 [317] and hsa-mir-155-5p [623] expression have been found to be altered in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%